HarPE™ Technical Briefs and Summaries 1989-1995 - Bandler, John W.; Biernacki, R.M.; Chen, S.H.; Zhang, Q.J. (Optimization Systems Associates, 1995)
HarPE™ is an advanced, powerful and user-friendly integrated CAD system dedicated to complete nonlinear device characterization and single device circuit simulations and design optimizations. Emerged from many years of theoretical research by Optimization Systems Associates Inc. HarPE was introduced as the world's first software system offering parameter extraction from harmonic measurements. HarPE offers a comprehensive approach to device-oriented CAD. It seamlessly integrates large-signal frequency-domain harmonic balance simulations with small-signal/DC simulations, using a unified circuit description. See, for example, Bandier, Biernacki, J. Song, Ye, and Zhang, "Analytically unified DC/small-signal/large-signal circuit design," IEEE Trans. Microwave Theory Tech., vol. 39, pp. 1076-1082, 1991. When needed, the small-signal parameters are automatically linearized from the nonlinear model. HarPE can simulate, optimize and accept as measurement data any combination of frequency-domain power spectra, DC IV characteristics, small-signal S parameters, as well as time-domain waveforms. The system allows you to carry out arbitrary combinations of bias, frequency and input power sweeps to investigate device behaviour or to accommodate multiple specifications for parameter extraction or design optimization. Sweeping arbitrary parameters is also possible. HarPE offers a truly nonlinear model device parameter extraction procedure which utilizes spectrum measurements, including DC bias information and output power at different harmonics measured under large-signal RF excitations. If large-signal measurements are not available, HarPE can extract the nonlinear model parameters from small-signal S parameters measured at a number of bias points, or even just from DC data (which alone is not sufficient to determine some parameters such as nonlinear capacitors). In general, HarPE accepts and utilizes all information from any combination of the three types of measurement data. The unique multi-circuit approach employed by HarPE increases the model identifiability and ensures a reliable and consistent solution suitable for large-signal, small-signal and DC simulation.
This document features technical briefs and summaries for HarPE™, an advanced, powerful and user-friendly integrated CAD system dedicated to complete nonlinear device characterization and single device circuit simulations and design optimizations. Emerged from many years of theoretical research by Optimization Systems Associates Inc. HarPE was introduced as the world's first software system offering parameter extraction from harmonic measurements. These technical briefs and summaries cover the period from June 7, 1989 to May 1, 1997, and describe the capabilities of HarPE ™ versions 1.0 to 2.0. Technical briefs of versions 1.0, 1.2, 1.4/1.4+S, 1.5/1.5+5, 1.7, 1.8, and 2.0 are available, as well as technical summaries of versions 1.0, 1.2, 1.3, and 1.4/1.4+S. See also technical briefs for Empipe™ and OSA90/hope™, manuals for other OSA products within the Optimization Systems Associates collection, and the OSA website archive at https://web.archive.org/web/19970413053327/http://osacad.com/osa.html .
Keywords: HarPE; Optimization Systems Associates; microwaves; FET; parameter extraction; Materka and Kacprzak model; Curtice and Ettenberg model; field-effect transistors; device modeling; L1, L2 optimization; small-signal measurements; S parameters; harmonic balance; HEMT models; Datapipe